Reputation: 970
Is it possible to prove
Lemma A3 (f x: Prop -> Prop)(y: Prop): f (x y) -> f y.
either w/ or (preferably) w/out axioms?
Upvotes: 1
Views: 64
Reputation: 970
The answer is "no" to proving w/out axioms (and I'm afraid it may be difficult to find meaningful axioms for proving it either). For suppose
Parameter A3: forall (f x:Prop->Prop)(y:Prop), f (x y) -> f y.
Definition f' (x:Prop) := x.
Definition X := fun _:Prop => True.
Check A3 f' X False: True -> False.
A3 f' X False
has type True -> False
, which is unprovable
Upvotes: 2